CASH: correlation-aware scheduling to mitigate soft error impact on heterogeneous multicores. Issue 2 (3rd April 2021) - Jiao, Jiajia; Wang, Libao; Li, Yanxiang; Han, Dezhi; Yao, Min; Li, Kuan-Ching; Jiang, Hai
Abstract : With the exponential increase in the number of transistors under fast-paced technology progress, the soft error induced reliability issue is becoming even more challenging in heterogeneous multicore processor design. As there are significant opportunities to mitigate the soft error impacts through heterogeneous multicore scheduling, we show in this paper that the correlation among multiple applications exhibits important reliability characteristics, by defining a new metric to measure the system-level vulnerability factor of multiple applications and an approximate estimator to evaluate the metric fast and accurately for effective scheduling decisions. To approach these issues, we propose CASH, a Correlation-Aware Scheduling strategy to optimise heterogeneous multicore system reliability. Comprehensive simulation results demonstrate that the proposed approach is promising, achieving up to 21.4% reliability improvement with only 3.6% performance degradation when compared with performance-oriented scheduling policy.